2021
DOI: 10.3389/fnut.2021.793795
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Responses of Cordyceps militaris to Salt Treatment During Cordycepins Production

Abstract: Cordycepin is a major bioactive compound found in Cordyceps militaris (C. militaris) that exhibits a broad spectrum of biological activities. Hence, it is potentially a bioactive ingredient of pharmaceutical and cosmetic products. However, overexploitation and low productivity of natural C. militaris is a barrier to commercialization, which leads to insufficient supply to meet its existing market demands. In this study, a preliminary study of distinct concentrations of salt treatments toward C. militaris was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 56 publications
(71 reference statements)
1
7
0
Order By: Relevance
“…An increase in NAA concentration increases the accumulation of toxic substances caused by serious damage to the cell membrane, reducing the ability to grow. During stress, the body undergoes major changes in morphology, and primary and secondary metabolites to adapt to the environment for survival, which is consistent with the corresponding physiological characteristics of Saccharomyces cerevisiae , Streptomyces caeruleus , and C. militaris (high salt stress) under stress conditions ( 37 39 ). The fruiting body undergoes different morphological, physiological, and molecular changes to adapt to the environment.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…An increase in NAA concentration increases the accumulation of toxic substances caused by serious damage to the cell membrane, reducing the ability to grow. During stress, the body undergoes major changes in morphology, and primary and secondary metabolites to adapt to the environment for survival, which is consistent with the corresponding physiological characteristics of Saccharomyces cerevisiae , Streptomyces caeruleus , and C. militaris (high salt stress) under stress conditions ( 37 39 ). The fruiting body undergoes different morphological, physiological, and molecular changes to adapt to the environment.…”
Section: Discussionsupporting
confidence: 72%
“…The C. militaris strain significantly enriches the biosynthesis pathway and glyceride metabolism pathway of unsaturated fatty acids under high salt conditions. Therefore, the reaction of C. militaris under NAA treatment is similar to that of S. cerevisiae and C. militaris under a high salt environment ( 39 ). As an important component of the cell membrane, lipids are highly sensitive to environmental changes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In support of this notion, our experiments under hyperosmotic conditions revealed that all three neutralized C. militaris strains underwent phenotypic degeneration, characterized by suppressed fruiting body and hyphal development, but increased conidia density and glycerol accumulation. Moreover, the radical growth of C. militaris and the expression of the Fus3 and Hog1 genes were repressed in a concentration-dependent manner under hyperosmotic conditions (42). Taken together, these findings suggest that the continuous activation of the HOG cascade under artificial culture conditions may lead to the dysregulation of MAPK pathway genes and phenotypic switching.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, C. militaris growth was inhibited by salt treatments, but COR production increased significantly with an increase in salt concentration. Transcriptome analysis of the salt-treated and control C. militaris groups revealed 3885 DEGs, among which DEGs associated with amino sugar and nucleotide sugar pathways were significantly enriched in the salt-treated group [51]. Salt treatment might increase energy molecule production and further promote COR accumulation.…”
Section: Militaris Transcriptome Analysismentioning
confidence: 95%